Rural School Psychology: Re-Opening the Discussion - Kerri L. Cloptom (Journal of Research in Rural Education, 2006)
The practice of school psychology in rural areas is a topic that has been fairly absent from the literature since the 1980s. A needs assessment of school psychologists practicing in rural counties in a midwestern state was conducted to explore current issues for rural school psychologists. The response rate for usable surveys was 72% (N = 106). Respondents answered questions regarding travel, supervision, professional development, practice, and the rewards and challenges of working in rural communities. The limited availability of support services in the community, feelings of professional isolation, work space, and travel time were issues of concern to the respondents. Recommendations, including implications for practitioners and trainers, are provided.